PEMBUATAN WEBSITE PANGKALAN SANTRI GUNA MENINGKATKAN SISTEM MANAJEMEN PONDOK PESANTREN DARUNNAJAH KECAMATAN BANDUNG KABUPATEN TULUNGAGUNG - Nathaniela, Amanda; Putri Anwar, Camelia Asiah; Nidhom Hidayah, Maulidiyah; Nabila Az-Zahro’, Syaikhhanun; Aliefia, Vony (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2024)
Information technology today has a significant impact in various aspects of people's lives, as it has become part of everyday life. However, in society, the reality is that the understanding and use of technology is still uneven in some areas. One of them is Darunnajah Islamic Boarding School, where there are obstacles in administrative bookkeeping and student management data that have no technology that facilitates data storage. Darunnajah Islamic Boarding School is an Islamic Education Institution in Bandung Subdistrict, Tulungagung Regency. The method of implementing this activity includes several stages, namely preparation and planning, field surveys and interviews, data collection, website design and development, training implementation and website handover, and evaluation. The result of this program is the establishment of a website for the students of Darunnajah Islamic Boarding School that can be accessed online by the Boarding School Admin and Walisantri as a strategic step in improving the quality of boarding school management, providing easy access to information